Principals’ Leadership in Improving School Committee Performance of Elementary School in Banda Raya Sub-District, Banda Aceh - Nuratiah, Nuratiah; AR, Murniati; Khairuddin, Khairuddin (FKIP Universitas Lampung, 2021)
Principals’ Leadership in Improving School Committee Performance of Elementary School in Banda Raya Sub-District, Banda Aceh. The purpose of this research is to describe program planning, principal’s strategies, and supporting factors to improving school committee’s performance of Elementary School in Cluster Langsat of Banda Raya sub-district of Banda Aceh. The study uses qualitative approach and descriptive method. Data were collected through observations, interviews, and documents. The subjects were principals, committee members, teachers and parents. The results show (1) school program planning was jointly decided through meeting held at the beginning of school year, involving principal, vice principal, teachers, committee members, and parents. According to observation results, activities were not well documented; (2) the principal strategies were by building effective communication with the committee, sharing information, and requesting committee’s approval; (3) supporting factors include good leadership communication skill, committee’s high commitment, and responsive in helping the school.Keywords: principal leadership, school committee performance, elementary school.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202104